Potential of Plant Extracts as Growth Exogenous Regulators of Potato Seeds - Fachirah Ulfa; Enny Lisan Sengin; Baharuddin Baharuddin; Syatrianti Andi Syaiful; Nadira R. Sennang; Rafiuddin Rafiuddin; Nurfaida Nurfaida; Ifayanti Ifayanti (Hasanuddin University, 2013)
Potato production in Indonesia has been declining while demand for potatoes remains increasing. One main reason of the decline is the lack of availability for good potato seedling. To optimize the growth of potato seedling, some plant extracts as exogenous growth regulators may be used. This experiment was aimed to select the best plant extract as exogenous growth regulator for potato seedling growth and study the underlying physiological process. Seven plant extracts as exogenous growth regulators for potato seedling were used as treatments namely: water as a control, corn grain (Zea mays L.), onion (Allium ascalonicum L.), coconut water (Cocos nucifera L), snaps (Phaseolus vulgaris L), banana (Musa paradisiaca L.) and mung bean sprouts (Vigna radiata). The experiment was set in the form of randomized complete block design with three replications. Result revealed that one month after sowing, corn grain extract gave the best quality on the potato seedling growth based on percentage of live seedling (100%), seedling height (15.87 cm), number of leaves (9.40 leaves) and root length of the seedlings (13.39 cm). On the other hand, water treatment (control) showed the lowest growth quality on potato seedling indicated in all parameters as follow: percentage of life of potatoes seedling (74.44%), seedling height (3.66 cm), amount of leaves (4.27 leaves) and length of root (4.83 cm).